The Influence of the Evolutionary Past on the Mind: An Analysis of the Preference for Landscapes in the Human Species - Moura, Joelson M. B.; Ferreira Júnior, Washington S.; Silva, Taline C.; Albuquerque, Ulysses P. (Frontiers in Psychology, 2018)
According to some evolutionary psychologists, landscapes preferences in the human species are influenced by their evolutionary past. Because the Pleistocene savanna is the least inhospitable landscape, it was the most suitable environment for survival and influenced the evolution of hominids in such a way that even today the human being has a universal preference for these environments. However, there is controversy regarding this statement, because in some studies it was evidenced that people prefer images of landscapes that are similar to those of the environment where they live. In this sense, we want to test whether there is indeed a preference for images of the savanna landscape and how the current environmental context may influence this preference. We performed a study in three environmental contexts with different landscapes in order to be able to observe the influence of the familiar landscape on landscape preference, of which two rural communities — one presenting a landscape similar to the deciduous seasonal forest and another presenting a savanna-like landscape — that totaled 132 participants and one urban community with 189 participants. The stimulus consisted of twelve images representing the six major terrestrial biomes and two images of urban landscapes. The variables analyzed were the emotional responses and the preference of the participants in relation to the images of landscapes. We analyzed the data using the Kruskal-Wallis test. The obtained result did not corroborate the idea of universal preference for images of savanna landscape. The image of Rainforest landscape was the preferred one among all the three environmental contexts studied. In this way, the preference for landscape may have been shaped at different periods of human evolutionary history, and not just during the period when hominids lived on the savannah. As much as selective pressures of the Pleistocene savanna have shaped the human mind during the evolutionary history, other factors and different types of environments may have influenced human preferences for landscapes.